2008
DOI: 10.1016/j.ajo.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Avellino Corneal Dystrophy Worsening after Laser In Situ Keratomileusis: Further Clinicopathologic Observations and Proposed Pathogenesis

Abstract: PURPOSE-To study the nature of the deposits in Avellino corneal dystrophy (ACD) worsening after laser in situ keratomileusis (LASIK), and suggest a mechanism for histopathogenesis. DESIGN-Interventional case report.METHODS-A 28-year-old woman previously diagnosed with bilateral ACD underwent bilateral LASIK. The corneal dystrophy progressively worsened bilaterally, one year later. A penetrating keratoplasty was subsequently performed on the right eye at 31 years of age, and in the left eye a year later. The cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…It has been reported that the mean time of exacerbation after excimer laser ablation procedure is 26 months and not exceeding 5 years. [4][5][6][7][8][9] In our patient, the cornea was clear before surgery and the clarity was maintained for 9 years after surgery. The most interesting part is how this heterozygous patient with ACD maintained the clarity of cornea for 9 years after PRK.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…It has been reported that the mean time of exacerbation after excimer laser ablation procedure is 26 months and not exceeding 5 years. [4][5][6][7][8][9] In our patient, the cornea was clear before surgery and the clarity was maintained for 9 years after surgery. The most interesting part is how this heterozygous patient with ACD maintained the clarity of cornea for 9 years after PRK.…”
Section: Discussionmentioning
confidence: 79%
“…ACD has been a closely watched issue since 2002 because of the exacerbation after laser in situ keratomileusis (LASIK). [4][5][6][7][8][9] Worsening or recurrence of ACD has also been reported after phototherapeutic keratectomy (PTK) and laser-assisted subepithelial keratomileusis. [10][11][12][13] Increased production of cytokines, including transforming growth factor-beta (TGF-b) after tissue removal with excimer laser, is thought to be a factor to worsen ACD.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The phenotypic appearance of granular corneal dystrophy (GCD) type 1 and GCD type 2 (also known as Avellino corneal dystrophy) changes with age, but is believed to also be influenced by trauma or intervening surgical procedures [123]. This report presents two cases of GCD, with varied manifestations before and after surgical intervention.…”
mentioning
confidence: 99%
“…Recurrence in the graft-host interface following DALK and lamellar keratoplasty is noted in the literature, and often granules will progress over time from the epithelium to the stroma [4]. Disease recurrence is well recognized in the graft-host interface area, and may be related to both GCD types, as well as surgical factors such as recurrence along suture tracks and incision lines [12345]. The exact reasons why recurrence is seen in some cases and not in others has yet to be elucidated.…”
mentioning
confidence: 99%